Evaluasi Toleransi terhadap Cekaman Aluminium pada Beberapa Galur Murni Kedelai - , Sunarto (Zuriat, 1993)
An Experiment was conducted to evaluate tolerancy to aluminium toxicity of several soybean pure lines generated from Dempo x wills on two levels of Al-Saturation of Red Yellow Podzolic soil. The experiment was arranged in a split plot design based on a randomized complete block design. The main plots were Al-saturation and the sub-plot were cultivars and pure lines. The result showed that T33, R22, and S4 were very tolerant to acid soil and Al-saturation.